Climate Change, Natural Disasters 2021 And the Impact on Insurance Demand! A Look at Germany from The Perspective of Behavioral Economics - Claudia PITTERLE (Communications of International Proceedings, 2022)
Natural disasters worldwide are becoming more extreme and more frequent. In Germany, the low-pressure area "Bernd" in the summer of 2021 caused costs of 40 billion dollars. An insurance against natural hazards protects against these risks and reimburses the costs incurred. From the perspective of the availability heuristic, insurance inquiries increase due to media presence after such severe catastrophes and then drop again. Despite increasing and severe natural catastrophes worldwide as well as in Germany, the insurance density of natural catastrophe insurances is only about 46%. The increasing danger is no longer perceived as the media presence decreases. And thus, the presentness of the danger should be made clearer.
Keywords: Natural Hazards; Insurance Demand; Heuristics; Subjective Risk Perception; Behavioral Economics